Scoping Review of Interventions to Promote Social Participation in Adolescents and Young Adults with Neurodisability - Conall O'Rourke; Mark Linden; Gary Bedell (Scholarworks @ WMU, 2020)
Background: Social participation, described as taking part in, being involvement and engaged with, and doing or being with others, is an important health outcome. Adolescents and young adults with neurodisability are often restricted in their social participation, particularly if they experience social and executive functioning challenges. A scoping review was conducted to examine interventions aimed at improving social participation in adolescents and young adults with neurodisability characterized by these challenges. Method: The scoping review included peer-reviewed empirical studies published from 1990 to 2016 that employed psychosocial interventions to improve social participation in young people 13 to 24 years of age with acquired brain injuries, autism spectrum disorders, and attention deficit disorders. Results: Narrative synthesis of 32 included studies highlighted significant variation in both the definition and measurement of social participation outcomes. The lack of RCT studies with large samples was noted, with almost a third of the studies including fewer than 10 participants. The two dominant types of intervention were peer mentoring and social skills training. Conclusion: There is a lack of rigorously tested interventions that specifically address social participation challenges for individuals with neurodisability. Future research will need to be clearer in how social participation is conceptualized and operationalized to allow for improved measurement and comparison between studies.